An assessment of the herd-level impact of the Theileria orientalis (Ikeda) epidemic of cattle in New Zealand, 2012–2013: a mixed methods approach. Issue 1 (2nd January 2016) - Vink, WD; Lawrence, K; McFadden, AMJ; Bingham, P
Abstract: AIM: To estimate incidence risk, cumulative mortality and case fatality rate within herds affected by bovine anaemia associated with Theileria orientalis infection (TABA), in New Zealand during the early phase of the epidemic (August 2012–September 2013). METHODS: A mixed methods approach was utilised to integrate data from various sources, including a detailed questionnaire carried out on 18 dairy farms which had experienced cases of TABA; a brief telephone survey of an additional 139 case farms; and data extracted from a Ministry for Primary Industries database for a further 42 case farms. The subsequent analysis determined incidence risk, cumulative mortality and case fatality rates for beef and dairy herds. RESULTS: Data were analysed from 196/263 (74%) known case farms at the date of closing the questionnaires. These farms contained 99, 505 cattle; 2, 847 animals were reported with clinical disease, and a further 590 animals were recorded as having died from TABA. The within-herd incidence risk, cumulative mortality and case fatality rate were consistent between the three data sources, did not differ between beef and dairy herds, and were estimated to be 0.97 (inter-quartile range (IQR) 0.36–2.07)%, 0.23 (IQR 0.00–0.66)% and 16.67 (IQR 0.00–33.33)%, respectively. There was substantial variability in the level of impact, with 22 farms severely affected (incidence risk >5% and cumulative mortality >5%). CONCLUSIONS: The mixed methods approach was effective in dealing with the disparate data sources. The inclusion of the majority of farms known to be affected at the time the questionnaires were performed implies that the information is likely to be representative. The collective outputs of the analyses represent the best estimate available of within-herd measures of disease frequency in the early phase of the epidemic in New Zealand. The limitations of the data imply that their primary application may be to inform the design of subsequent structured observational field studies. CLINICAL RELEVANCE: The results of this study provide information on the impact of TABA on cattle farms during the emergence and early spread of the disease, as well as for generating hypotheses on causal mechanisms and risk factors that may influence the course of disease.